Symptom report and treatment experience of hypogonadal men with and without type 2 diabetes in a United States health plan. Issue 7 (9th April 2015) - Shortridge, E. F.; Polzer, P.; Donga, P.; Wade, R. L.
Summary Background Although hypogonadism (HG) is interrelated with type 2 diabetes mellitus (T2DM), there is little information about men's experiences with HG, T2DM, and testosterone replacement therapy (TRT). We examined symptoms and TRT use among men with HG, with and without T2DM, who received care within a single United States health plan. Methods Men aged ≥ 18 years with HG, with and without T2DM, were identified from the 2008 to 2010 Reliant Medical Group electronic medical record database. Surveys responses compared by T2DM status using chi‐square or Wilcoxon rank sum tests. Results A total of 93 men were included (19 with HG and T2DM, 74 with HG only). Men with both HG and T2DM were more frequently treated for their HG by an endocrinologist (52.6%), compared with men with HG only (28.4%, p = 0.058). Erectile dysfunction (ED) was the primary reason for seeking care among all surveyed men, although men with HG and T2DM reported experiencing ED more often (94.7%) than men with HG only (46.0%, p < 0.0001). Additional reasons for seeking care were similar between cohorts and included loss of energy and decreased sex drive. Most men (88.2%) reported using TRT, primarily as injection or gel formulations. Discontinuation of TRT was reported slightly more frequently by men with HG and T2DM (68.4%), compared with men with HG only (55.4%, p > 0.05). Conclusions This study provides information about symptoms and TRT utilisation among HG men with and without T2DM. Men with HG only were less likely than those with both HG and T2DM to report that they were currently experiencing key symptoms compared with when they were first diagnosed, regardless of TRT utilisation, and were less likely to report ED as a current symptom.